Studi Prevalensi dan Faktor yang Berhubungan dengan Diabetes Melitus di Provinsi Jambi: Analisis Data Riskesdas 2018 - Deski Pratiwi; M.Dody Izhar; Muhammad Syukri (Jurnal Kesehatan Komunitas, 2022)
The prevalence of diabetes melitus in Jambi Province has increased from 1.2% in 2013 to 1.4% in 2018. This study aims to determine the factors associated with the incidence of diabetes melitus in Jambi Province. This cross-sectional study used 2018 Basic Health Research (Riskesdas) data. Data regarding gender, age, smoking status, physical activity, nutritional status, and hypertension from 14,296 respondents were analyzed. The relationship between independent variables and the incidence of diabetes melitus was analyzed bivariately using the Chi-square test (X2) followed by multivariate analysis using the Multiple Logistics Regression Test. The results showed that the prevalence of diabetes melitus in Jambi Province was 1.5%. Factors associated with diabetes melitus were age (AOR = 4.058; 95% CI = 2.409-6.837) and hypertension (AOR = 1.841; 95% CI = 1.192-2.841). This study found that age was the dominant factor in the incidence of diabetes melitus in Jambi Province. The prevalence of diabetes melitus can be reduced by conducting regular health checks (blood sugar, blood pressure, and cholesterol), stopping smoking, diligent physical activity, a healthy and balanced diet, and adequate rest, especially in the age group ≥45 years.